CRITERIA AND LEVELS OF DEVELOPMENT OF PROFESSIONAL SELF-REFLECTION OF FUTURE LEADER OF AN INSTRUMENTAL BAND - Mazur D. V. (International Journal of Innovative Technologies in Social Science, 2020)
This article examines the state and criteria of development of professional self- reflection of future leaders of an instrumental bands. The qualitative characteristic of levels of development of professional self-reflection is defined and four levels of development of this skill are outlined. The value and role of professional self-reflection of the leader of an instrumental band in the context of collective performance management is disclosed. It is noted that the reflexive method makes it possible to comprehend one’s own and team members’ activities, to predict one’s own actions, to form a new thinking style, to detect and anticipate problems in one’s own professional activities and improve the quality of work. We also believe that professional reflection is a necessary component of the professional education of the future leader of the instrumental ensemble and the cornerstone principle of successful management of any ensemble performance in particular.